2014
DOI: 10.1093/bioinformatics/btu327
|View full text |Cite
|
Sign up to set email alerts
|

Exploring protein domain organization by recognition of secondary structure packing interfaces

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Since domains are the basic functional units of proteins (Deng et al, 2014), we identified domains in SPs. We scanned the SPs using InterPorScan (Jones et al, 2014) (version 57) based on eleven integrative protein family databases, including Pfam, CATH-Gene3D, PIRSF, PROSITE, HAMAP, PRINTS, ProDom, SMART, TIGRFAMs, SUPERFAMILY, and PANTHER.…”
Section: Resultsmentioning
confidence: 99%
“…Since domains are the basic functional units of proteins (Deng et al, 2014), we identified domains in SPs. We scanned the SPs using InterPorScan (Jones et al, 2014) (version 57) based on eleven integrative protein family databases, including Pfam, CATH-Gene3D, PIRSF, PROSITE, HAMAP, PRINTS, ProDom, SMART, TIGRFAMs, SUPERFAMILY, and PANTHER.…”
Section: Resultsmentioning
confidence: 99%